DETERMINING THE VENDING MACHINE PURCHASING EXPERIENCE TOWARDS CUSTOMER SATISFACTION AMONG UNIVERSITY STUDENTS - Mimi Nadhirah binti Aszhar; Muhammad Amirul Firdaus bin Asri; Noorazlin binti Ramli; Fatimah binti Abd Ghani (International Journal of Accounting, Finance and Business, 2022)
Vending machine utilization can give customers easy, autonomous services and is available 24 hours a day. The primary goal of this study is to determine the relationship between vending machine purchasing experiences and customer satisfaction and the most influential determinants. Mode of payment, vending machine condition, vending machine maintenance, product assortment, and product freshness were evaluated. Data is collected from 364 consumers in the UiTM Terengganu campus via an online survey. This study focuses on three Terengganu campuses: UiTM Dungun, UiTM Bukit Besi, and UiTM Kuala Terengganu. Frequency analysis, descriptive analysis, and multiple regression analysis were performed. Machine maintenance is an essential aspect determining consumer satisfaction when purchasing via vending machines. As a result, the findings of this study can assist vending machine retailers in preserving customer loyalty, acquiring new consumers, and helping the company to thrive in the future.